Senderismo del litoral y paisaje turístico en la Parroquia Chacarita del cantón Ventanas de la Provincia de Los Ríos - Barco Poveda, Angeline Yessenia (2019)
Trekking is an activity that is practiced in an open and easy way, it will show how it is linked to the conservation and well-being of both nature and people, it is a reason to initiate deep research that helps the development of this flexibility tour. The tourist landscapes are the complement to the practice of this activity due to the characteristics that it possesses, and the demand that tourists emit for having the pleasure of contemplating the natural resources, the fauna, the flora, entering their space without the worry of get lost on the road However, the problem of wasting tourist landscapes causes the existence of reduced hiking in coastal areas, resulting in limited development of tourism activities in rural areas, which are the richest in natural components. The Chacarita parish is rich in characteristics that demand the hiking modality, such as landscapes, abundant vegetation, reliefs, among other resources, is the research point of this project, where the proposal is based on the demand that tourists emit, being this a path that allows you to recognize all the wonders of this ecosystem. For the practice of hiking there are several recommendations or indications that help to have a better experience when developing technology, tourist luggage, the guide, clothing in general is the main indication or the rule that the practitioner must meet to avoid Any type of anomalies. The load capacity in terms of the guide is a rule that must be respected, to maintain the care of the ground and the natural structure of the area in which hiking mobility is performed